A half century of didactic design in mathematics education: A bibliometric analysis - Fardian, Dilham; Suryadi, Didi; Prabawanto, Sufyani; Putri, Amelia Defrianti; Qamariah, Nur (Jurnal Gantang, 2024)
This study aims to examine the results of studies on didactic design in mathematics education as a contribution to the advancement of study concerning didactical design research. 1413 research articles on didactic design in mathematics education indexed in Scopus over the past 50 years, from 1973 to 2024, were collected and analyzed using bibliometric analysis. The results show increased studies related to didactic design in mathematics education. Based on the bibliometric analysis using VOSviewer and RStudio, there was a significant increase in publication between 2016 and 2022 but a decrease in 2023. The most frequently appearing keywords in the VOSviewer and RStudio search are “mathematics education," “teaching," and “mathematics." However, a relationship exists between didactic design and elementary education, secondary school, and higher education. The correlation on these labels is small, presenting opportunities for research on didactic design. From the visualization using VOSviewer and RStudio, research related to didactic design in algebra, calculus, and geometry has not been done much, and it is very urgent to do so because the potential research on didactic design in these areas is up-and- coming.